2021
DOI: 10.1093/intqhc/mzab161
|View full text |Cite
|
Sign up to set email alerts
|

Incident Reporting Reduction during the Covid-19 Pandemic in a Tertiary Italian Hospital. A Retrospective Analysis

Abstract: Background Incident reporting (IR) is one of the most used systems to gain knowledge of AEs and to identify sources of risk. During COVID-19 pandemic, several organizational changes have been implemented to respond adequately and effectively to the emergency; this required the suspension of most deferrable activities. The aim of this study is to investigate whether incident reporting attitude of health workers has been reduced during the pandemic event. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…We did not find similar reports in the literature to support our research data probably because the issue of intention to report a near-miss event is not widely published in general, particularly not during the COVID-19 crisis. However, this finding is similar to results in other studies that examined perception of patient safety culture during COVID-19 14,16,17. Some of the data are also consistent with studies completed before COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We did not find similar reports in the literature to support our research data probably because the issue of intention to report a near-miss event is not widely published in general, particularly not during the COVID-19 crisis. However, this finding is similar to results in other studies that examined perception of patient safety culture during COVID-19 14,16,17. Some of the data are also consistent with studies completed before COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…16 In this specific study, the actual infrastructure of the hospital was found to be lacking, in terms of the building, water and electricity breaks, beds without sides, and oxygen bottles without a stand and not well secured to the wall. 16 A significant positive relationship was found between most components of patient safety culture and intentions to report near-miss events, similar to other studies. 5,10,11,20 Years of experience was the only demographic data point that showed a significantly positive relationship with all 3 components of patient safety culture, intention to report a near-miss event, and actual reporting of near-miss events.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nursing staff turnover, specifically in L&D, resulted in additional use of contract nurse who may not report incidents as often. The increasing demands place on staff during the pandemic potentially reduced reporting opportunities or impacted safety attitudes (Denning et al, 2020;Pauletti et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%